On Optimality of Regular SAFER+ and Modified SAFER+ Diffusion - Knarik M. Kyuregyan (Изд-во НАН РА)
In this paper it is shown that the regular block cipher SAFER+ and modified SAFER+ provide an optimal diffusion in the sense that ciphers are resistant against differential cryptanalysis attack after minimum possible number of rounds. Moreover, there are 967 680 byte permutations that provide equivalent security.
Keywords: Mathematics; Computer software